How sensitive is the recovery of stratospheric ozone to changes in concentrations of very short-lived bromocarbons? - Yang, X.; Abraham, N. L.; Archibald, A. T.; Braesicke, P.; Keeble, J.; Telford, P. J.; Warwick, N. J.; Pyle, J. A. (Atmospheric Chemistry and Physics, 2018)
Naturally produced very short-lived substances (VSLS) account for almost a quarter of the current stratospheric inorganic bromine, Br y . Following VSLS oxidation, bromine radicals (Br and BrO) can catalytically destroy ozone. The extent to which possible increases in surface emissions or transport of these VSLS bromocarbons to the stratosphere could counteract the effect of halogen reductions under the Montreal Protocol is an important policy question. Here, by using a chemistry–climate model, UM-UKCA, we investigate the impact of a hypothetical doubling (an increase of 5 ppt Br y ) of VSLS bromocarbons on ozone and how the resulting ozone changes depend on the background concentrations of chlorine and bromine. Our model experiments indicate that for the 5 ppt increase in Br y from VSLS, the ozone decrease in the lowermost stratosphere of the Southern Hemisphere (SH) may reach up to 10% in the annual mean; the ozone decrease in the Northern Hemisphere (NH) is smaller (4–6%). The largest impact on the ozone column is found in the Antarctic spring. There is a significantly larger ozone decrease following the doubling of the VSLS burden under a high stratospheric chlorine background than under a low chlorine background, indicating the importance of the inter-halogen reactions. For example, the decline in the high-latitude, lower-stratospheric ozone concentration as a function of Br y is higher by about 30–40% when stratospheric Cl y is ~ 3 ppb (present day), compared with Cl y of ~ 0.8 ppb (a pre-industrial or projected future situation). Bromine will play an important role in the future ozone layer. However, even if bromine levels from natural VSLS were to increase significantly later this century, changes in the concentration of ozone will likely be dominated by the decrease in anthropogenic chlorine. Our calculation suggests that for a 5 ppt increase in Br y from VSLS, the Antarctic ozone hole recovery date could be delayed by approximately 6–8 years, depending on Cl y levels.